EOSINOPHILIC VARIANT OF CLEAR CELL RENAL CELL CARCINOMA - A DIAGNOSTIC DILEMMA - RAO, NAMRATA; MONAPPA, VIDYA; K, SUMAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Introduction: Eosinophilic variant of clear cell renal cell carcinoma is an important entity to diagnose since it is aggressive and is associated with poor prognosis. Case Report: A 75-year-old patient presented with pain abdomen. The magnetic resonance imaging showed a mass in the kidney. The differential diagnosis given was renal cell carcinoma and hydatid cyst. Nephrectomy was done and the specimen was sent for histopathology. The specimen showed a gray-brown lesion with extensive areas of hemorrhage and necrosis. On microscopy, the tumor cells were arranged in nests. The cells had abundant eosinophilic granular cytoplasm. The differential diagnosis on morphology was chromophobe renal cell carcinoma and oncocytoma with extensive inflammation. However, immunohistochemistry (IHC) proved the diagnosis of eosinophilic variant of clear cell renal cell carcinoma. Conclusion: Hence, IHC is an essential adjunct to morphology in diagnosing renal neoplasms.